Is agricultural production correlated with labour force? Case study on Romania - Rujescu, Ciprian Ioan; Feher, Andrea (Acta Carolus Robertus, 2022)
The aim of the article is to analyse the correlations between the volume of labour in agriculture and the value of some indicators of agricultural production. The volume of the labour force in Romania, between 2007 and until now, can be represented by a chronological series with a decreasing trend. The value of agricultural production, show an inverse trend, more precisely, the period in which the volume of labour was high corresponds to a period with a low value of agricultural productions, and vice versa. The paper contains discussions of possible interactions between these data series, analysed from a statistical point of view. Discussions on the possible causes underlying the relationships between the studied indicators can also be found.